2023
DOI: 10.1097/aog.0000000000005286
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Human Papillomavirus Non-16/18, Type-Specific Risk for Cervical Intraepithelial Neoplasia Grade 3 or Worse Among Women With Cervical Atypical Glandular Cells

Abstract: OBJECTIVE: To evaluate the risk for cervical intraepithelial neoplasia grade 3 (CIN 3) or worse (including adenocarcinoma in situ [AIS] and invasive cervical cancer) associated with non-16/18 human papillomavirus (HPV) types (other HPV) among women with atypical glandular cells (AGC) in cervical cytology. METHODS: This population-based cohort study evaluates the risk of CIN 3 or worse associated with other HPV types. Human papillomavirus genotyping was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Furthermore, HPV16 and HPV18 have been the most prevalent genotypes identified in AGC cases. 69 Yilmaz et al reported the five most common types in their cohort were HPV16 (19.8%), HPV18 (15.6%), HPV31 (9.5%), HPV45 (5.8%) and HPV52 (4.4%), while Tang et al identified HPV16 (16.7%), HPV18 (9.5%), HPV52 (7.1%), HPV58 (6.6%) and HPV53 (3.6%) in their study population. 66 69 A study from Italy revealed HPV58 and HPV31 to be the most common types after HPV16 and HPV18.…”
Section: Hpv Genotypes In Cervical Cytologymentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, HPV16 and HPV18 have been the most prevalent genotypes identified in AGC cases. 69 Yilmaz et al reported the five most common types in their cohort were HPV16 (19.8%), HPV18 (15.6%), HPV31 (9.5%), HPV45 (5.8%) and HPV52 (4.4%), while Tang et al identified HPV16 (16.7%), HPV18 (9.5%), HPV52 (7.1%), HPV58 (6.6%) and HPV53 (3.6%) in their study population. 66 69 A study from Italy revealed HPV58 and HPV31 to be the most common types after HPV16 and HPV18.…”
Section: Hpv Genotypes In Cervical Cytologymentioning
confidence: 99%
“… 69 Yilmaz et al reported the five most common types in their cohort were HPV16 (19.8%), HPV18 (15.6%), HPV31 (9.5%), HPV45 (5.8%) and HPV52 (4.4%), while Tang et al identified HPV16 (16.7%), HPV18 (9.5%), HPV52 (7.1%), HPV58 (6.6%) and HPV53 (3.6%) in their study population. 66 69 A study from Italy revealed HPV58 and HPV31 to be the most common types after HPV16 and HPV18. 70 In the study of AGC by Pradhan et al , the most severe lesion was CIN2/3 (5.6%), followed by endometrial carcinoma (5.5%) and endocervical lesions (1.3% for AIS, 0.6% for ADC) after histological follow-up within 1 year.…”
Section: Hpv Genotypes In Cervical Cytologymentioning
confidence: 99%
See 1 more Smart Citation